Scheduling in a flexible job shop followed by some parallel assembly stations considering lot streaming. Issue 4 (3rd April 2022) - Daneshamooz, Fatemeh; Fattahi, Parviz; Hosseini, Seyed Mohammad Hassan
ABSTRACT: This article presents a flexible job-shop scheduling problem with a parallel assembly stage and lot streaming. Suppose that several products of different kinds are ordered to be produced. Each product consists of several specific parts. The components (parts) of products are manufactured in a flexible job shop, then assembled into products in parallel lines or parallel stations. The objective function is to minimize the total completion time of products (makespan). First, the problem is described and the parameters and decision variables are defined. Then, the problem is modelled as a mixed-integer linear programming model to solve the problem using GAMS software. Owing to the NP-hardness of the problem, two new algorithms are proposed to solve it for medium- and large-sized instances. These algorithms are based on variable neighbourhood search (VNS), with self-adaptive parallel VNS being applied in one of them. The considered problem is decomposed into two subproblems and each algorithm is used on two levels. These algorithms are applied to solve test problems of different sizes. The results show that the two-level algorithms perform better than the integrated one and the algorithm with self-adaptive parallel VNS outperforms the other algorithms in terms of solution quality.